2000
DOI: 10.1211/0022357001773977
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Permeation by Multidrug-resistance-modulators and Non-modulators: Effects of Hydrophobicity and Electric Charge

Abstract: This study was designed to test the hypothesis that lipophilic cationic drugs with only roughly similar structures mediate the reversal of multidrug-resistance (MDR) by interacting with membrane phospholipids. The permeation properties of MDR-modulators and non-modulators were studied by quantifying their ability to induce the leakage of Sulphan blue through the membrane of negatively charged unilamellar liposomes. Of the 22 compounds under investigation, only those bearing a net positive electric charge per m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Moreover, pretreatment with nifedipine, an MDR PGP inhibitor, prevents the hippocampal GR upregulation induced by antidepressants (Przegalinski et al, 1993). Inhibition of PGP and other membrane steroid transporters is not receptor mediated and is related to the drugs' physiochemical properties, that is, lipophilicity, electric charge, and ability to accept hydrogen bonds (Ford, 1996;Castaing et al, 2000;Ekins et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pretreatment with nifedipine, an MDR PGP inhibitor, prevents the hippocampal GR upregulation induced by antidepressants (Przegalinski et al, 1993). Inhibition of PGP and other membrane steroid transporters is not receptor mediated and is related to the drugs' physiochemical properties, that is, lipophilicity, electric charge, and ability to accept hydrogen bonds (Ford, 1996;Castaing et al, 2000;Ekins et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Further work has clarified that most antidepressants, including SSRI's, enhance cortisol action in the brain and periphery by inhibiting membrane steroid transporters that regulate the intracellular concentration of cortisol, principally by expelling cortisol from the cell (Pariante et al, 1997(Pariante et al, , 2003aWeiss et al, 2003). Although membrane steroid transporter inhibition has been shown to occur independently of glucocorticoid-receptor mediation, and instead, is affected directly by the physiochemical properties of antidepressants (Ford, 1996;Castaing et al, 2000;Ekins et al, 2002), this action could result in an augmentation of negative feedback inhibition of the HPA axisFan effect consistent with the reversal of at least one known perturbation in MDDFreduced negative feedback inhibition (Nemeroff, 1996;Holsboer, 2000;McQuade and Young, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…By this way, membrane permeability could be increased. In a study, it was reported that calmodulin antagonists such as clomipramine and thioridazine, calcium channel blocker such as verapamil, beta adrenergic receptor blocker, propranolol and also antiparasitic agents like quinine are very effective whereas steroids and antineoplastic agents are not effective in influencing the membrane permeability (Castaing et al, 2000). Furthermore, bioactive sphingolipid levels are also altered in anticancer drug-resistant cancer cells (Ogretmen & Hannun, 2004).…”
Section: Alterations In Membrane Lipidsmentioning
confidence: 99%